2017
DOI: 10.1007/s12288-017-0804-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Interleukin-9 Expression as a Potential Therapeutic Target in Chronic Lymphocytic Leukemia in a Cohort of Egyptian Patients

Abstract: There was an overexpression of IL-9 in CLL patients that correlated with modified Rai staging, ZAP70, CD38 and all hallmarks of an active and aggressive disease. The correlation between IL-9 upregulation and patient characteristics provided direct clinical evidence for its contribution to the pathogenesis of CLL. In conclusion, significantly higher expression of IL-9 measured at both the mRNA and the protein levels in patients with CLL that correlates with more complex course of the disease and worse prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The altered expression of IL-9 evaluated at both the mRNA and protein levels has been reported in biopsies and in the serum of B-CLL patients [127]. This increase correlated with Rai staging, ZAP70, and CD38 [128].…”
Section: Effects Of Cytokines On the Onset Progression And Complicamentioning
confidence: 91%
“…The altered expression of IL-9 evaluated at both the mRNA and protein levels has been reported in biopsies and in the serum of B-CLL patients [127]. This increase correlated with Rai staging, ZAP70, and CD38 [128].…”
Section: Effects Of Cytokines On the Onset Progression And Complicamentioning
confidence: 91%
“…Intravenous injection of monoclonal anti-IL-9 antibodies was proven effective in ameliorating disease outcomes in the Eμ-TCL1/p66Shc −/− mouse model of aggressive CLL [ 15 ], paving the way to further pre-clinical studies. In the era of targeted therapies, the strong association between circulating IL-9 and markers of unfavorable CLL prognosis [ 14 , 15 , 90 ] suggests the potential use of anti-IL-9 antibodies as a therapeutic option for patients with high IL-9 levels. Interestingly glucocorticoids, potent immune-suppressive agents that reduce cytokine expression by inhibiting transcription factors such as Activation Protein (AP)-1 and NF-κB, have been observed to reduce IL-9 expression in asthma patients [ 40 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…We and others recently reported the overexpression of IL-9 in leukemic cells from CLL patients [ 14 , 15 , 90 , 91 , 92 ] and Eμ-TCL1 mice [ 15 ], a well-established CLL mouse model [ 93 ]. Interestingly, this enhanced expression correlates with hallmarks of aggressive disease, such as unmutated Immunoglobulin Heavy Variable (IgHV) genes, ectopic expression of ζ-associated protein of 70 kDa (ZAP-70), and high levels of the surface glycoprotein CD38 [ 14 , 15 , 90 ]. Moreover, it correlates with lower overall survival of CLL patients [ 15 ].…”
Section: Il-9 Acts As a Pro-tumoral Soluble Factor In Chronic Lymphocytic Leukemia (Cll)mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has revealed that IL-9 plays a role in neoplastic proliferation, particularly in lymphomagenesis [ 13 ]. Studies examined biopsies and serum samples from patients with B-cell chronic lymphocytic leukemia (CLL) and found that the levels of IL-9 mRNA and protein expression were altered and correlated with Rai staging, ZAP70, and CD38 [ 28 ]. This was confirmed in further studies, where IL-9 expression was detected in the serum of 20 out of 47 CLL patients but was not detectable in control subjects [ 29 ].…”
Section: Role Of Cytokines In Chronic Lymphocytic Leukemiamentioning
confidence: 99%